Evaluation of Air Voids in Concrete Based on Cross-Section Images of Its Test Specimens - Vasyl Lozynskyi; Iryna Ivasenko; Roman Vorobel; Olena Berehulyak; Teodor Mandziy; Taras Voronyak; Yaroslav Ivanytskyi; Oleksandr Maksymenko; Liubomyr Ropyak (Buildings)
Concrete is a material that is widely used in construction and other industries due to its strength and durability. Many characteristics of concrete that are important for its operation, in particular crack resistance, frost resistance, and water resistance, directly depend on the distribution structure and percentage of air voids in concrete. The problem of assessing air voids in concrete based on images of sections of their test samples is considered, the solution of which is relevant for determining the grade of concrete during non-destructive testing of building structures and critical infrastructure facilities. A three-dimensional modelling of the distribution of air voids in concrete was carried out based on a uniform distribution for different air content percentages, which made it possible to substantiate the reliability of assessing the three-dimensional distribution of air voids from two-dimensional images. A method for assessing air content based on the Otsu segmentation-method with subsequent filtering out by geometric shape has been developed. It was tested on real images of sections of test concrete samples. The presented results of experimental studies demonstrate an increase in the reliability of air voids segmentation in images of cross-sections of concrete test specimens using the proposed method, and make it possible to state that the percentage of air voids can indicate concrete strength.